Myofascial pain: from Virchow's to our days - I. V. Egorov (Неврология, нейропсихиатрия, психосоматика, 2014)
Myalgia is not a definite nosological entity and fixes the attention of neurologists, rheumatologists, and physicians in other specialties. This is first of all associated with the high incidence of chronic pain syndrome that leads to long-term disability mainly in young and middle-aged persons. One of the most common reasons for seeking advice from a therapist and neurologist is low back pain that may be due to the involvement of three key anatomical players: facet joints (arthrosis treatment should make an emphasis on  hondroprotectors), intervertebral disks (in case of discopathy, clinicians tend to favor nonsteroidal anti-inflammatory drugs – NSAIDs), and a muscular frame. In this case, two thirds of patients with pain syndromes in the trunk and limbs are found to have myofascial dysfunction that is defined as impaired function of one orother muscle, which occurs with its overload and manifests itself as muscle spasm and the presence of painful muscle infiltrations or local muscle hypertonus and trigger points in the tense muscles. Ignoring this fact gives rise to the irrational use of analgesic and anti-inflammatory drugs and further to the increase of their doses because the treatment is ineffective. Modern-day therapy for myofascial syndrome is multimodal and encompasses physiotherapic and manual procedures and the use of myorelaxants rather than NSAIDs. To prescribe myorelaxants, it is necessary to understand their mechanisms of action and the effects of different agents in this group.